The effects of a mobile application for patient participation to improve patient safety - Nam‐Ju Lee; Shinae Ahn; Miseon Lee (Wiley, 2022)
Abstract Background Patient participation in patient safety activities in care processes is a fundamental element of safer care. Patients play an important role in preventing patient safety incidents and improving health outcomes. Therefore, healthcare providers need to develop and provide educational materials and actionable tools for patient participation. Objectives This study aimed to develop a mobile application for health consumers' participation and evaluate the effect of the mobile application on improving health consumers' participation in patient safety. Methods A quasi‐experimental design was adopted. We developed a mobile application on the basis of a needs assessment, literature review, compilation of patient safety topics, and validity testing of the application. The target population included Korean adults aged between 30 and 65 years who had visited a medical institution more than once within the most recent 6 months. The intervention group received patient participation training by using the mobile application, Application for Patient Participation in Safety Enhancement, for 2 months. The primary outcome variables were patient safety knowledge, self‐efficacy of participation, willingness to participate and experience of patient participation in patient safety activities. End‐user satisfaction was assessed using a questionnaire. To assess participants' experiences with the intervention, qualitative data were collected through a focus group interview and open‐ended responses to an end‐user satisfaction survey. Results The intervention group (n = 60) had significantly higher overall average scores than the control group (n = 37) with regard to patient safety knowledge (p < .001), self‐efficacy of participation (p = .001), willingness to participate (p = .010) and experience of participation (p = .038) in the post‐survey. The total mean end‐user satisfaction score was 3.56 ± 0.60. The participants expressed the realization that patients could play an important role in improving patient safety. Conclusions This study demonstrated that educating health consumers through a mobile application with useful information improves patient participation in patient safety activities. Educational materials and patient participation tools could motivate health consumers' health‐related behaviours. Patient or Public Contribution Patients were involved during the programme development and evaluation.